PENGUKURAN KUALITAS INFORMASI PENGUKURAN KUALITAS SISTEM INFORMASI ADMINISTRASI VAKSIN (SIAVI) IMUNISASI - Fikri Faidul Jihad; Eko Sediyono; Nurjazuli (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The Health Service requires an accurate, comprehensive, and efficient immunization vaccine administration information system (SIAVI) to support better immunization vaccine recording and reporting, as well as to assist policymakers in planning, managing vaccine stocks, and managing vaccine distribution to public health center. The West Aceh District Health Office was in charge of developing the immunization vaccine administration information system (SIAVI). The focus of this research was to compare the quality of information provided by users of the system before and after it was developed, using a weighted average. A questionnaire was used as a research instrument in this study. The questionnaire, which was provided to seven people, contained 15 questions categorized into 5 categories: completeness, convenience, suitability, and timeliness. Based on the weighted average calculation, the overall value of information quality before system development is 2.27, and after system development is 3.36, with a difference of 1.09, indicating that there is a difference between before and after system development, and it can be concluded that the administrative information system immunization vaccine (SIAVI) has a good information quality aspect and can be used as an application and operated by the immunization program manager at the Health Office.